Sensitivity to drying and storage of Syzygium cumini (L.) Skeels - Myrtaceae seeds - Muxfeldt, Rejane Elize; Tonetti, Olívia Alvina Oliveira; Silva , Edvaldo Aparecido Amaral da; Pimentel , Cleise Rebelo; José, Anderson Cleiton; Faria, José Marcio Rocha (Revista de Ciências Agroveterinárias, 2024)
Syzygium cumini seeds are recalcitrant, thus cannot tolerate drying and storage. The aim of this study was to evaluate the longevity of these seeds under different storage conditions and to assess the effect of osmotic treatment with polyethylene glycol (PEG) and abscisic acid (ABA) on reducing sensitivity to desiccation and increasing the longevity of these seeds. Seeds were desiccated until they reached preestablished moisture contents (40, 35, 30, 25 and 15%) and allowed to germinate. With 25% moisture content, germination was approximately 40%, and, with 15%, germination did not occur anymore. In the treatments aimed at reducing sensitivity to desiccation, seeds were incubated for 15 days in a solution of PEG (-1.88 MPa) or PEG (-1.88 MPa) + ABA (10-4 M), desiccated until they reached the preestablished moisture contents mentioned above, and then allowed to germinate. Five conditions were tested for storage: plastic bag in a cold room (8-10 °C; 45% RH); plastic bag in an air-conditioned room (20 °C; 60% RH); paper bag at room temperature; PEG solution at -1.88 MPa at 20 °C; and PEG solution at -1.88 MPa + ABA 10-4 M at 20 °C. Germination tests were carried out after 15, 30 and 90 days of storage. The best storage condition was in a plastic bag in an air-conditioned room, which was capable to keep a germinate rate close to 100% for up to 90 days. Under the conditions tested, osmotic treatment with or without ABA did not reduce sensitivity to desiccation and did not prolong seed longevity.